THE RIGHT TO VOTE AND THE AUSTRALIAN CONSTITUTION - Sifris, Ronli (Revista da Faculdade de Direito do Sul de Minas, 2012)
Australia is a democracy. Therefore, the right to vote is an integral component of the Australian system of government. Thus it may come as a surprise that the Commonwealth Constitution does not contain an express right to vote. In the absence of an express constitutional right to vote, the High Court has nevertheless recognized that such a right is essential to ensuring the system of representative government established by the Commonwealth Constitution. Accordingly, along with the implied freedom of political communication, the High Court has found that the right to vote is inherent in sections 7 and 24 of the Commonwealth Constitution which require that the Parliament be “directly chosen by the people”. This article begins by providing a contextual overview of the Commonwealth Constitution. It then examines the concept of rights in Australian constitutional law. After noting that there are four express rights in the Commonwealth Constitution, the article turns to a discussion of the concept of implied rights before focusing on the implied right to vote. Discussion of the right to vote concentrates on the two High Court decisions which have established that there is a constitutionally entrenched right to vote in Australia: Roach v Electoral Commissioner¹ and Rowe v. Electoral Commissioner².